PENGARUH PENGETAHUAN TENTANG MENOPOUSE DENGAN KECEMASAN MENGHADAPI MENOPOUSE PADA WANITA DI KELURAHAN SUMBER SURAKARTA - Rusmeirina, Cepty (TALENTA, 2014)
Menopause is  a  natural phase  that  will be  faced  by  women over  the age of  40years.  Where does this  mark the end of  a womans  fertile period.  Menopausal syndromeexperienced by many women because it takes an understanding. The purpose of this studywas to determine  the presence or absence  of  knowledge about  the effects of  menopausewith  anxiety  facing  menopause  in women.  The population  in this study were  all  women aged  40  years  -  65  years  in the Village  Source  Surakarta.  The sampling technique usedwas  simple  random  sampling.  The  study  was  conducted  using  primary  data  andsecondary data. Analysis of  the data  in this study consists  of  two  parts: a descriptive  andcorrelational analysis. Based on the data analysis it can be concluded  that there is a  significant positive relationship  between  knowledge  of menopause in  women  with  anxiety  is r  =  0.729;  p  =0.000  (p  <0.05),  which  means  that  the higher the level  of knowledge  about  menopause, the lower the  anxiety levels  of women  in the  Source  Surakarta.  Effective contribution  tothe  variable  knowledge  about  menopause  anxiety  by  53.1%  indicated  the  determinant coefficient  (r2)  of  0.531.  Meanwhile,  46.9%  influenced  by  other  factors  such as  family support, social-economic, cultural and lifestyle characteristics.